2009
DOI: 10.1002/asia.200800427
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Proteins at Cysteine: Opportunities in Chemistry and Biology

Abstract: Chemical modification of proteins is a rapidly expanding area in chemical biology. Selective installation of biochemical probes has led to a better understanding of natural protein modification and macromolecular function. In other cases such chemical alterations have changed the protein function entirely. Additionally, tethering therapeutic cargo to proteins has proven invaluable in campaigns against disease. For controlled, selective access to such modified proteins, a unique chemical handle is required. Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
535
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(563 citation statements)
references
References 111 publications
3
535
0
13
Order By: Relevance
“…We chose lysine as a competing nucleophile since it is the most abundant nucleophile found in proteins, it is more widely used in synthetic polypeptides compared to histidine or cysteine, and it is known to compete with thiol and imidazole groups in protein alkylations. 27,28 Similar to results obtained in other Met alkylations, 15 we found that the Met residues in the copolymer could be alkylated chemoselectively with glycidyl azide in acidic media in the presence of a fourfold excess of amine groups (eq. 2).…”
Section: Glycosylation (Procedures C)supporting
confidence: 83%
“…We chose lysine as a competing nucleophile since it is the most abundant nucleophile found in proteins, it is more widely used in synthetic polypeptides compared to histidine or cysteine, and it is known to compete with thiol and imidazole groups in protein alkylations. 27,28 Similar to results obtained in other Met alkylations, 15 we found that the Met residues in the copolymer could be alkylated chemoselectively with glycidyl azide in acidic media in the presence of a fourfold excess of amine groups (eq. 2).…”
Section: Glycosylation (Procedures C)supporting
confidence: 83%
“…As the most robustly nucleophilic of the 20 canonical amino acids, the thiol of cysteine offers a unique reactive handle within proteins, a property exploited extensively in nature 1 . Although pH may need to be controlled, selective reaction at cysteine over other nucleophilic residues such as lysine and histidine can be achieved 14 , while the low abundance (o2%) of cysteine in proteins often allows for facile modification at a single site 3 . In addition to functionalization of a protein of interest, this can also allow ready mutational repositioning and codon reassignment (through Cys-Ser/Gly mutation) 15 .…”
Section: Modifications Of Natural Amino Acidsmentioning
confidence: 99%
“…The UAA dehydroalanine (Dha) can be used as a Michael acceptor and has found extensive use in protein modification, reacting rapidly with sulfur nucleophiles to generate alkyl cysteine analogues, offering an electrophilic alternative to nucleophilic reaction of cysteine 3 . This is particularly useful in examples where use of electrophilic alkylation of Cys is difficult to control or where appropriate electrophiles cannot be generated, and leads to a greater level of selectivity.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Numerous strategies, including biological 8 and chemical synthesis, 1,2 have been developed to either react with or modify natural residues, or replace them entirely, using highly selective processes. Many of these methods have focused on reaction at or replacement of L-cysteine (Cys), 9 L-methionine (Met), 8,10,11 and N-terminal residues 12,13 since these are often present in low abundance and thus can provide unique sites for functional modification. Most chemical strategies have focused on reactions at highly nucleophilic Cys thiol groups, where a variety of different types of modification are possible.…”
Section: Introductionmentioning
confidence: 99%